Studi Literatur: Implementasi Teori Belajar Behaviorisme dan Humanisme serta Tantangan dalam Konteks Pendidikan: Penelitian - Lerin Erzian; Mariati Purnama Simanjuntak; Renata Pasaribu; Grace Nurlela Napitupulu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Modern education faces dual challenges: implementing effective learning theories while preserving national identity amid the currents of globalization. This study aims to analyze the implementation of behaviorism and humanism learning theories, as well as to examine the challenges arising in the educational context. The method employed is a literature study with a descriptive qualitative approach, collecting and synthesizing findings from 20 relevant journals. The results show that behaviorism is effective in developing specific skills and measurable behaviors through stimulus–response mechanisms and reinforcement. Meanwhile, humanism excels in fostering self-potential, intrinsic motivation, empathy, and meaningful, student-centered learning. The integration of both theories can create holistic learning. On the other hand, globalization poses challenges such as the weakening of national identity due to the influence of foreign cultures. In conclusion, the implementation of learning theories needs to be integrated with character education, civic education, and the reinforcement of Pancasila values to build a generation that is academically competent while maintaining a strong national identity.